Pengaruh Dry Heat Treatment Dan Pengokeran Terhadap Pertumbuhan Dan Kesehatan Bibit Cabai Rawit (Capsicum Frutescens L.) - NI KADEK AYU WIDAYANTHI; I GUSTI NGURAH RAKA; I KETUT SIADI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2017)
Effect of Dry Heat Treatment and Container on Seeds Growth and health of Chilli Pepper (Capsicum frutescens L.)The dry heat treatment (DHT) technology had improve that it can inactivation viruses disease on seed, so it have to implement in seedling for production of healty seeds. This study was aims to determine of influense of DHT and container agains chilli papper of seed growth which healty and resistence against environment condition in fields. The design used in this study was completely randomized design with 4 treatments and 6 replications. The treatments were combined clod DHT, DHT combination of polybags, non-dry heat treatment (NDHT) clod or the ability of local farmers, and the NDHT combination polybags. The variables measured in this study include, germination, chlorophyll content, number of leaves, plant height, leaf area, root length, fresh weight and oven dry weight. The results showed that clod DHT most effective in producing healthy chilli papper seeds and able to adapt in the field. While NDHT was not effective in producing healthy chilli seeds and not able to adapt in the field.